Trajectory Analysis Of Ball Based On Image Processing And Simulation - Anthony Louis, Stephanie (2017)
This dissertation is about trajectory analysis of ball based on image processing and simulation. Data used in this dissertation are two videos to determine the initial parameters that can affect the trajectory of the table tennis ball and football. Objective of this dissertation is to plot and analyse the trajectory of balls. Image processing techniques were used to capture the projection. The motivation of this research is to determine the existence of spin in a trajectory where the initial parameters are unknown. The first video was a high speed video captured at 1000 frame per second. The high speed video captured the initial projection of a table tennis ball. The spin is unknown; therefore through Matlab simulations the existence of spin is determined. Initial parameters from the video are computed in order to replicate the projectile mathematically. The second video is a broadcasting video that captured at approximately 30 frames per second. This video was analysed in a three dimensional view to determine the existence of spin. The type of spin whether the football was experiencing topspin, backspin or sidespin was also analysed. The findings of this dissertation shows the existence of topspin when the table tennis ball was launched. The football in the video had a backspin while moving in the y-z direction. The projectile of the football and table tennis ball is successfully plotted.